Development of Spectrophotometric Methods for Iodide Determination Using Hydrogen Peroxide (H2O2) as Oxidizing - Abner Tonu Lema; Hermin Sulistyarti; Atikah Atikah (Natural B, Journal of Health and Environmental Sciences, 2014)
Serious disorders of iodine deficiency can cause irreversible cretinism, pregnancy complications, goiter, compromised thyroid hormone production, mental impairment and decreasing cognitive function. In order to detect early indication of Iodine Deficiency Disorders (IDD) a development of simple spectrophotometric method for iodide  determination  is proposed using hydrogen peroxide (H2O2) as an oxidizing agent. Determination of iodide is based on the oxidation reaction of I- to I2 that form blue  complex compound I2-starch. The blue color intensity of the complex I2-starch  produced was measured at wavelength of 611 nm. Several parameters were optimized: complex formation and oxidation time of iodide, the optimum concentration of oxidizing agent, H2SO4, starch and effect of interfering ions (chloride, bromide, thiocyanate), with optimum conditions obtained of respectively: 10 minute, H2O2 0.1 M, H2SO4 0.05 M, starch 0.2 %. Under these condition, the method showed linearity of 5 - 60 ppm, limit of detection and quantification of 0.62 and 2.09 mg/L, respectively. This method has been successfully applied to synthetic and urine samples and can be recommended for the detection of iodide in patients hyperthyroidism and KI tablets.